A Comparative Study of Capacitance Properties with Different Polydioxythiophene - A. Melvin, Ambrose (Asian Journal of Chemistry, 2013)
Polydioxythiophenes such as 3,4-ethylenedioxythiophene (PEDOT), 3,4-propylenedioxythiophene (ProDOT) and dimethyl-3,4-propylenedioxythiophene (dimethyl-ProDOT) had been electrodeposited by potentiostatic method over indium tin oxide (ITO) surface for comparative electrochemical capacitance measurement. Weight of the polymer deposited by potentiostatic method is estimated by determining the charge consumed during the process. A symmetrical parallel plate electrochemical cell was used for capacitance measurement. The solvent and electrolytes used were propylene carbonate (PC) and tetrabutylammonium perchlorate (TBAP), respectively. Value of capacitance is highest in case of PEDOT followed by ProDOT and dimethyProDOT, however, power density follows the reverse trend. High capacitance of PEDOT with slow charge/discharge is because of compact coiled nature of the polymer film. This facilitates the movement of the ion in and out of the polymer film. In contrast to that ProDOT and dimethyl ProDOT has porous nature which allows the fast movement of ion through the polymer film. Fast movement of the ion reduce the stability of polymer in case of ProDOT and dimethyl-ProDOT, however, in case of PEDOT capacitance remain stable after several redox cycle. A comparative analysis of all the three polymers reveals that PEDOT is better in terms of energy density, when compared to ProDOT and dimethyl-ProDOT that exceed in term of power density, for future capacitor fabrication.